Far from home : a novel - Steel, Danielle (New York : Random House Large Print, 2025)
"In July 1944, Arielle von Auspeck arrives at the glamorous Hotel Ritz in occupied Paris. Half French, half German, she is happy to be back in France, where her husband, Gregor, a retired colonel, will join her soon from Germany. Arielle and Gregor have thus far been able to hide their private opposition to Hitler. Then her world falls apart."--
Keywords: Widows -- Fiction; World War, 1929-1945 -- France -- Fiction; Underground movements -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction; Historical fiction; Large print books